2009
DOI: 10.1186/cc7129
|View full text |Cite
|
Sign up to set email alerts
|

Bench-to-bedside review: The importance of the precision of the reference technique in method comparison studies – with specific reference to the measurement of cardiac output

Abstract: Bland-Altman analysis is used for assessing agreement between two measurements of the same clinical variable. In the field of cardiac output monitoring, its results, in terms of bias and limits of agreement, are often difficult to interpret, leading clinicians to use a cutoff of 30% in the percentage error in order to decide whether a new technique may be considered a good alternative. This percentage error of ± 30% arises from the assumption that the commonly used reference technique, intermittent thermodilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
274
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(281 citation statements)
references
References 21 publications
6
274
1
Order By: Relevance
“…Imprecise data may lead to erroneous judgments; if a monitoring device or technique is highly precise, it will be able to detect small changes in a variable. However, if it is imprecise, it will only be able to detect much larger changes [25]. Therefore, it is necessary to establish the number of injections that are required for a measurement to achieve a statistically relevant level of precision and least significant change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Imprecise data may lead to erroneous judgments; if a monitoring device or technique is highly precise, it will be able to detect small changes in a variable. However, if it is imprecise, it will only be able to detect much larger changes [25]. Therefore, it is necessary to establish the number of injections that are required for a measurement to achieve a statistically relevant level of precision and least significant change.…”
Section: Discussionmentioning
confidence: 99%
“…Precision is considered to be 'good' when variability due to random error in the measurements is low [25]. The coefficient of variation was determined and then used to calculate the precision and the least significant change.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The benchmark at ±30 % (±28.3 % to be more precise) refers to the assumption that intermittent thermodilution (ITD) by the pulmonary artery catheter has a precision of ±20 % and means that if PE lies within a range of ±30 %, methods are interchangeable with ITD as they show a comparable individual error. In this study, TEE showed a superior precision (7.2 %) than ITD and, consequently, redetermining the range of an acceptable PE could be considered [3]. Claiming the new methods to have at least the same individual error as the TEE would result in an acceptable PE of ±10.2 %.…”
mentioning
confidence: 75%